A clear urban–rural gradient of allergic rhinitis in a population-based study in Northern Europe. Issue 1 (1st January 2016) - Christensen, Stine Holmegaard; Timm, Signe; Janson, Christer; Benediktsdóttir, Bryndis; Forsberg, Bertil; Holm, Mathias; Jogi, Rain; Johannessen, Ane; Omenaas, Ernst; Sigsgaard, Torben; Svanes, Cecilie; Schlünssen, Vivi
Abstract : Background: The protective effect of farm upbringing on allergic rhinitis is well known, but how upbringing in other environments influences the development of allergic rhinitis is scarcely investigated. The aim of this study was to investigate the association between place of upbringing and pet keeping in childhood and allergic rhinitis and nasal symptoms in adulthood. Methods: The population-based Respiratory Health in Northern Europe study includes subjects from Denmark, Norway, Sweden, Iceland, and Estonia born in 1945–1973. This paper analyses 13, 376 participants of the third study wave. Six categories of place of upbringing were defined: farm with livestock, farm without livestock, village in rural area, small town, city suburb, and inner city. Pets in the home at birth and during childhood were recorded. Data were analysed using adjusted logistic regression models. Results: Livestock farm upbringing predicted less adult allergic rhinitis [odds ratio (OR) 0.68, 0.54–0.85] and nasal symptoms (OR 0.82, 0.68–0.99) than city upbringing, and an urban–rural gradient with decreasing risk per level of urbanisation was observed (OR 0.92, 0.88–0.94). Pets in the home at birth (OR 0.78, 0.68–0.88) and during childhood (OR 0.83, 0.74–0.93) were associated with less subsequent allergic rhinitis. Pet keeping did not explain the protective effect of place of upbringing. Conclusion: Risk of allergic rhinitis and nasal symptoms in adulthood was inversely associated with the level of urbanisation during upbringing. Pets at birth decreased the risk further, but did not explain the urban–rural gradient. Persistent beneficial effects of microbial diversity in early life might be an explanation for the findings.